An Investigation of Monolayer As1−xPx Solid Solutions: From a Theoretical Perspective. Issue 26 (17th August 2022) - Ma, Xiaoyang; Li, Dechun
Abstract: Phase stability and disordered solid solutions should be noticed in theoretical works due to the operating temperature up to several hundred Kelvin in the normal growth process. To better understand the properties of monolayer As1− x P x solid solutions, the phase diagram and properties of both ordered and disordered structures are investigated from a theoretical perspective. It is found that monolayer As1− x P x prefer phase‐separating structures at low temperatures and will form disordered solid solutions with temperature elevating. Considering that random atomic arrangement will destroy the inner symmetry of structures, disordered solid solutions are expected to hold piezoelectric properties which are not available in the phase‐separating ordered structures. The strains induced properties are examined which could give a detailed picture of the electronic and catalytic properties. Here, the systematic investigation of As1− x P x will be valuable for understanding monolayer As1− x P x solid solutions and is believed to set a tone for applications in further electronics and optoelectronic applications. Abstract : The solid solutions of AsP can be formed with temperature elevating. The random atomic arrangement in disordered solid solutions will destroy its inner symmetry. Without inversion centers, the related odd‐rank tensor properties, such as the third‐rank piezoelectric tensor, could be nonzero as a mathematical consequence, thus, can inspire the piezoenhanced excitonic or photoelectric properties of AsP solid solutions.